Effect of an Electromagnetic Fuel-Saving Device on Motorcycles Using Blended fuel of Pertalite-bioethanol - Todaro, Muhammad; Nufus, Tatun Hayatun; Susanto, Iwan; Siregar, Rolan (President University, 2024)
The increasing demand for fuel efficiency and environmental sustainability has led to the exploration of alternative fuel blends and innovative fuel-saving technologies. This study investigates the effect of an electromagnetic fuel-saving device on the performance of a motorcycle using a Pertalite-Bioethanol fuel blend at different compositions (P100, P90, P80, and P70). The engine's performance was evaluated based on Maximum Torque, Brake Horse Power (BHP), and Specific Fuel Consumption (SFC) using a chassis dynamometer test. The results show that the use of the electromagnetic fuel-saving device significantly improves motorcycle performance. The highest torque was recorded at P80, reaching 13.52 Nm with the device, compared to 12.7 Nm without the device. Similarly, BHP at P80 increased from 7.45 HP (without device) to 9.89 HP (with device), indicating enhanced combustion efficiency. Additionally, SFC was lower when using the device, with the lowest fuel consumption observed at P80 (0.025 kg/HP·h with the device), compared to 0.029 kg/HP·h without it. These findings suggest that a 20% bioethanol blend (P80) provides an optimal balance of power, torque, and fuel efficiency, particularly when combined with electromagnetic fuel treatment. However, at higher bioethanol concentrations (P70), performance slightly declined, likely due to the lower energy content of ethanol compared to gasoline. The improvement in efficiency with the electromagnetic device is attributed to the enhanced dispersion of hydrocarbon molecules, leading to better combustion. The electromagnetic fuel-saving device effectively enhances engine performance and fuel efficiency, particularly when paired with a 20% bioethanol blend. This study provides valuable insights into the potential of alternative fuel treatments in improving combustion efficiency and sustainability. Future research could focus on long-term durability, emissions analysis, and further optimization of bioethanol fuel blends for improved engine performance.Keywords: Electromagnetic fuel-saving device, Pertalite-Bioethanol blend, Motorcycle performance, Fuel efficiency.